Supracostal access: Does it affect tubeless percutaneous nephrolithotomy efficacy and safety? - Jun-Ou J. (2017)
Introduction: Tubeless percutaneous nephrolithotomy (PCNL) in selected patients has been found to be safe and can reduce postoperative discomfort without increasing complications. The challenges of tubeless PCNL via supracostal access are inadequate drainage and postoperative bleeding, conditions that may increase pulmonary complications. We compare the efficacy and safety of the tubeless supracostal versus the standard supracostal PCNL. Materials and Methods: Supracostal PCNL with one percutaneous renal access, no significant bleeding, extravasation and residual stone was performed in 95 patients. Of these, 43 were tubeless PCNL (Group-I) and 52 were PCNL with standard routine postoperative nephrostomy tube (Group-II). In group-I, PCNL was done by the standard supracostal technique with the placement of a postoperative external ureteral catheter for 48 hours. The operative time, success rate, hospital stay and ensuing complications were compared between group-I and group-II. Results: Patients in the tubeless PCNL group (Group-I) were 90.7% stone -free while those with standard routine postoperative nephrostomy tube(Group-II) were 84.6% stone -free. Additionally, stone fragments of less than 4 mm in diameter were found in 9.3% of patients in group-I and 25.4% in group-II. The success rate, hematocrit change and complication were not significantly different between both groups. The analgesic requirement, operative time and hospital stay were all significantly less in the tubeless supracostal group (Group-I). None of group I and only one patient of group II needed intercostal drainage. Conclusion: Tubeless supracostal percutaneous nephrolithotomy in selected patients is effective with acceptable complications. This technique offers the advantage of lower analgesic requirement, shorter operative time and hospital stay. The pulmonary complication is the same as the standard supracostal percutaneous nephrolithotomy.